2016
DOI: 10.1371/journal.pone.0166550
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Agreement between Radiomic Features Computed for Multiple CT Imaging Settings

Abstract: ObjectivesRadiomics utilizes quantitative image features (QIFs) to characterize tumor phenotype. In practice, radiological images are obtained from different vendors’ equipment using various imaging acquisition settings. Our objective was to assess the inter-setting agreement of QIFs computed from CT images by varying two parameters, slice thickness and reconstruction algorithm.Materials and MethodsCT images from an IRB-approved/HIPAA-compliant study assessing thirty-two lung cancer patients were included for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 30 publications
4
102
0
1
Order By: Relevance
“…Several studies already showed that radiomic feature values are influenced by image acquisition and reconstruction settings, like slice thickness and exposure [2,[9][10][11][12][13]. For instance, Mackin et al [13] scanned a phantom with ten unique inserts using different acquisition parameters on computed tomography (CT) scanners of four manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies already showed that radiomic feature values are influenced by image acquisition and reconstruction settings, like slice thickness and exposure [2,[9][10][11][12][13]. For instance, Mackin et al [13] scanned a phantom with ten unique inserts using different acquisition parameters on computed tomography (CT) scanners of four manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major limitations in quantitative image analysis and radiomics, however, is the wide variability and lack of uniformity across institutions, scanner platforms, 74 slice thickness, 75 reconstruction kernels, 76 other acquisition parameters, and even nodule segmentations. 9,77,78 …”
Section: Radiomics As a Novel Tool To Quantitatively Analyze Tumor Immentioning
confidence: 99%
“…Assessing variability of radiomics features for imaging equipment or its different settings is an important topic and has been studied for non small cell lung cancers in different studies (Lu, Ehmke, Schwartz, & Zhao, 2016; Mackin et al, 2015; Zhao et al, 2016) and in breast MRI based lesion classification (Chen et al, 2010). Repeated CT scans of the same patient in the same day were used to assess reproducibility of a set of feature in (Lu et al, 2016; Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Repeated CT scans of the same patient in the same day were used to assess reproducibility of a set of feature in (Lu et al, 2016; Zhao et al, 2016). The study in (Mackin et al, 2015) focused on the comparison of imaging features from patients and phantoms computed using 17 different scans of the phantom (used as ground truth).…”
Section: Introductionmentioning
confidence: 99%